Surveillance and Documentation of Fruit Flies Parasitoids from Infested Fruits Collected from District Larkana and Hyderabad: Survey and documentation of bio-control agents from Sindh - Abro, Zain-Ul-Aabdin; Baloch, Naheed; Memon, Raza Muhammad; Khuhro, Niaz Hussain; Soomro, Qadeer Ahmed (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Fruit flies belong to family (Tephritidae-Diptera) are the most injurious fruit pests of the fruits and vegetables. Biological control is an environmental friendly control method that has been used against pest fruit flies. Parasitoids have been one of the most widely used groups of natural enemies. In present studies we have surveyed the biological control agents from two different zones of Sindh. The field locations were Hyderabad and Larkana districts from where infested fruits were collected from guava and mango orchards. The results revealed that significantly (P<0.05) higher number of larval cum pupal parasitoid Trybliographa daci were (62.2 ± 3.03, 50.20 ± 4.45) recorded in guava from both districts. Furthermore, Maximum number of Bactrocera zonata infestation was recorded (395.6 ± 4.50, 288.00 ± 11.57) from guava orchards of both districts. This study established that Larval/pupal parasitoid Trybliographa daci proved most promising biocontrol-agent in limiting the population of fruit flies in guava and guava observed most susceptible host for fruit flies in terms of infestation.